High performance silicon photonic devices based on practical metamaterials - Halir, Robert; Luque-González, José Manuel; Sánchez-Postigo, Alejandro; Herrero-Bermello, Alaine; González-Andrade, David; Hadij-El-Houati, Abdelfettah; Leuermann, Jonas; Pereira-Martín, Daniel; Ortega-Moñux, Alejandro; Ctyroky, Jiri; Wanguemert-Pérez, Juan Gonzalo; Velasco, Aitor V.; et al. (My University, 2019)
Subwavelength grating metamaterials are enabling a new generation of high-performance silicon photonic devices. Here we discuss the fundamental physics along with some of the latest advances in this rapidly expanding field.
Robert Halir, et al., "High performance silicon photonic devices based on practical metamaterials," OECC/PSC, 7-12 July 2019, Fukuoka (Japan)
Keywords: Optoelectrónica; Comunicaciones; Congresos y conferencias; Si photonic and heterogeneous platform, Advanced Passive Devices, Optical filters, Optical polarization control devices, Novel Materials and Platform for Passive Devices; Si photonic and heterogeneous platform; Advanced Passive Devices; Optical filters; Optical polarization control devices; Novel Materials and Platform for Passive Devices